Language Development and Building Character Early Children through Role Playing Method - Novalina, Sesti; Anwar, Khairul; Maharani, Ria; Suryani, Dewi; Sari, Diana; Hariandi, Rizki (CV. Creative Tugu Pena, 2024)
The purpose of this research is to explain the role-playing method in the process of language development and building children's character from an early age. Role playing is expected to be able to have an effect on the early childhood education process so that it contributes to the control of early childhood education in Indonesia. References are obtained through literature review in order to obtain sources related to the data needed for analysis and then conclusions. Role playing is able to develop language and build character, through the roles played by children it is easier to interact and have the opportunity to play various kinds of characters so as to provide appropriate learning to build character so that they are able to directly differentiate between good and bad roles. The rampant actions of children against parents, teachers and bullying and the lack of maximum implementation of character education values in children is the background for research and is a special concern and must be immediately taken seriously by educators. Keywords: Language Development, Role Playing Method, Building Character Children